Oxytetracycline age validation of an adult shortfin mako shark Isurus oxyrinchus after 6years at liberty - Kinney, M J; Wells, R J D; Kohin, S (Journal of fish biology, 2016)
This study presents findings on an oxytetracycline injected adult male shortfin mako Isurus oxyrinchus recaptured in waters off of southern California after 6years at liberty. During the period at liberty, the vertebral band-pair deposition rate was validated at one per year. This result indicates that from a time at or near sexual maturity, male I. oxyrinchus in the north-east Pacific Ocean exhibit a band-pair deposition rate of one band pair per year, while deposition rates for juveniles in the area have been validated at two band pairs per year.